Strategies for Organizational Intervention to Develop a World-Class Company - Vargas-Hernández, José G.; Miranda, M. I. Julián Adolfo Adame (Global Disclosure of Economics and Business, 2016)
The aim of this paper is to present the case of organizational intervention in the monopolistic state-owned company, the Federal Electricity Commission (CFE). Here are presented the diagnosis of the CFE, the strategies in place to make it a world-class company and the results obtained. The trial follows the methodology of Organizational Intervention (Vargas-Hernandez, 2014); i.e. in three main areas that constitute the components of the classic strategic model of organizations (Vargas-Hernandez, p.44): the organizational structure axis, the axis of processes / technologies and mainly the third axis corresponding human behavior. [El objetivo de este trabajo es presentar el caso de intervención organizacional en la empresa monopólica del Estado, la Comisión Federal de Electricidad (CFE). Se presentan el diagnóstico de la CFE, las estrategias establecidas para convertirla en una empresa de clase mundial y los resultados obtenidos. El ensayo sigue la metodología de Intervención Organizacional (Vargas-Hernández, 2014); es decir, en tres grandes ejes que constituyen, los componentes del modelo estratégico clásico de las organizaciones (Vargas-Hernández, p. 44): el eje de estructura organizacional, el eje de los procesos/tecnologías y principalmente, el tercer eje que corresponde al comportamiento humano.]